EVALUASI KELAYAKAN FINANSIAL USAHA SUSU KAMBING SEGAR LABANY DI KOTA METRO - Kinasih, Arum Sekar; Prasmatiwi, Fembriarti Erry; Murniati, Ktut; Situmorang, Suriaty (Lampung University, 2025)
This study aims to evaluate the financial and non-financial feasibility in Labany fresh goat milk business in Metro City. This research was conducted from January to February 2025. The research method utilized in this study was a case study method. The Respondents in this study were consisted of various people including the owner of fresh milk business, five employees, three residents, and two consumers. The data analysis method used was financial feasibility analysis by calculating investment criteria including NPV, IRR, Gross B/C, Net B/C and Payback Period and for non-financial analysis using descriptive analysis by analyzing technical aspects, economic and market aspects, social engineering, and the environment. The results of the financial analysis of Labany goat milk business are profitable and feasible to develop. Based on the sensitivity scenario, cost changes have a maximum limit of 58 percent, while cost increases have a limit of 90 percent. Meanwhile, based on non-financial analysis involved technical aspects, economic and market aspects, social engineering aspects, and environmental technical aspects, Labany goat milk business is very feasible to run. Key words: feasibility, goat milk, risk , sensitivity analysis